Nineteenth-Century Radical Traditions
XV, 243 p. 1 illus.
Keywords: This book takes a fresh look at the progressive interventions of writers in the nineteenth century. From Cobbett to Dickens and George Eliot, and including a host of lesser known figures – popular novelists, poets, journalists, political activists – writers shared a commitment to exploring the potential of literature as a medium in which to imagine new and better worlds. The essays in this volume ask how we should understand these interventions and what are their legacies in the twentieth and twenty first centuries? Inspired by the work of the radical literary scholar, the late Sally Ledger, this volume provides a commentary on the political traditions that underpin the literature of this complex period, and examines the interpretive methods that are needed to understand them. This timely book contributes to our appreciation of the radical traditions that underpin our literary past.